Handbook of research on combating threats to media freedom and journalist safety - Jamil, Sadia, 1984- (Advances in media, entertainment, and the arts (AMEA) book series., 2020)
"This book evaluates how diverse threats impact journalists' safety, their right to freedom of expression, and overall media freedom in various contexts. It also addresses inadequacies in national security policies, planning, and coordination relating to the safety of journalists in different countries"--